Bilateral femur metastases in low‐grade endometrial carcinoma. Issue 7 (25th May 2015) - Lunardi, Pierre; Vidal, Fabien; Accadbled, Franck; Leguevaque, Pierre; Soule‐Tholy, Marc; Beauval, Jean Baptiste; Motton, Stéphanie
Key Clinical Message Lower‐limb bone metastases are uncommon in low‐grade endometrial carcinoma, and are mostly located on the axial skeleton. Here, we present a rare case of bilateral femur metastases in low‐grade endometrial carcinoma and performed a review of the current literature.